Altered Phenylpropanoid Metabolism in the Maize Lc-Expressed Sweet Potato (Ipomoea batatas) Affects Storage Root Development - Wang, Hongxia (Nature Publishing Group, 2016)
There is no direct evidence of the effect of lignin metabolism on early storage root development in sweet potato. In this study, we found that heterologous expression of the maize leaf color (Lc) gene in sweet potato increased anthocyanin pigment accumulation in the whole plant and resulted in reduced size with an increased length/width ratio, low yield and less starch content in the early storage roots. RT-PCR analysis revealed dramatic up-regulation of the genes involved in the lignin biosynthesis pathway in developing storage roots, leading to greater lignin content in the Lc transgenic lines, compared to the wild type. This was also evidenced by the enhanced lignification of vascular cells in the early storage roots. Furthermore, increased expression of the β-amylase gene in leaves and storage roots also accelerated starch degradation and increased the sugar use efficiency, providing more energy and carbohydrate sources for lignin biosynthesis in the Lc transgenic sweet potato. Lesser starch accumulation was observed in the developing storage roots at the initiation stage in the Lc plants. Our study provides experimental evidence of the basic carbohydrate metabolism underlying the development of storage roots, which is the transformation of lignin biosynthesis to starch biosynthesis.